2010
DOI: 10.1017/s0954422410000089
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid receptor 2 and nutrient sensing: a proposed role for fibre, fermentable carbohydrates and short-chain fatty acids in appetite regulation

Abstract: The way in which the composition of the diet may affect appetite, food intake and body weight is now receiving considerable attention in a bid to halt the global year-on-year rise in obesity prevalence. Epidemiological evidence suggests that populations who follow a fibre-rich, traditional diet are likely to have a lower body weight and improved metabolic parameters than their Western-diet counterparts. The colonic effects of fibre, and more specifically the SCFA that the fermentation process produces, may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
145
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(149 citation statements)
references
References 122 publications
1
145
0
3
Order By: Relevance
“…Similarly, the higher consumption of fruits, vegetables and dairy products within the Traditional Lebanese pattern may increase the intakes of several nutrients and phytochemicals, including fibre and calcium (Ca) [39]. By decreasing dietary energy density, increasing satiety, buffering insulin fluctuations, and increasing the production of short-chain fatty acids, dietary fibre may pay a role in appetite and weight regulation [43]. Similarly, calcium has been suggested to play a role in body weight regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the higher consumption of fruits, vegetables and dairy products within the Traditional Lebanese pattern may increase the intakes of several nutrients and phytochemicals, including fibre and calcium (Ca) [39]. By decreasing dietary energy density, increasing satiety, buffering insulin fluctuations, and increasing the production of short-chain fatty acids, dietary fibre may pay a role in appetite and weight regulation [43]. Similarly, calcium has been suggested to play a role in body weight regulation.…”
Section: Discussionmentioning
confidence: 99%
“…GPR41 is another SCFA receptor. Binding to GPR41 is associated with upregulation of peptide YY (PYY) and glucagon-like peptide 1 [(GLP1), anorectic hormones] that have effects on appetite control; therefore, SCFAs are linked to food intake by activating these receptors (78,79). Current evidence indicates that SCFAs have paradoxical effects on hepatic health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the consumption of inulin, galacto-oligosaccharides, and raffinose stimulates F. prausnitzii (119-121). F. prausnitzii, which belong to the butyrate-producing bacteria, could be crucial to gut barrier function and could modulate systemic inflammation (common to NAFLD) (79,122). All of these proposed actions may play a role in the beneficial effects of prebiotics in NAFLD prevention and/or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Sleeth et al indicated that the binding of SCFAs to FFA2 and FFA3 located on L-cells may participate in controlling glucagon-like peptide 1 (GLP-1). 30) In contrast, another study reported that SCFAs have no effect on GLP-1 in vivo. 31) Besides, Paiva et al indicated that acarbose treatment did not change the gene expression of sodium glucose cotransporter 1 (SGLT1) and glucose transporter 2 (GLUT2) but increased GLUT1 protein by 75% in middle small intestine.…”
mentioning
confidence: 97%